Is It Race, Class, or Gender? The Sources of Perceived Discrimination in Brazil. (2nd January 2018) - Layton, Matthew L.; Smith, Amy Erica
Abstract: Observers have long noted Brazil's distinctive racial politics: the coexistence of relatively integrated race relations and a national ideology of "racial democracy" with deep social inequalities along color lines. Those defending a vision of a nonracist Brazil attribute such inequalities to mechanisms perpetuating class distinctions. This article examines how members of disadvantaged groups perceive their disadvantage and what determines self-reports of discriminatory experiences, using 2010 AmericasBarometer data. About a third of respondents reported experiencing discrimination. Consistent with Brazilian national myths, respondents were much more likely to report discrimination due to their class than to their race. Nonetheless, the respondent's skin color, as coded by the interviewer, was a strong determinant of reporting class as well as race and gender discrimination. Race is more strongly associated with perceived "class" discrimination than is household wealth, education, or region of residence; female gender intensifies the association between color and discrimination.